THE VALUES OF ISLAMIC RELIGIOUS EDUCATION IN THE PERSPECTIVE OF THE AL-QURAN TO BUILD CIVIL SOCIETY AT THE MODERN AN NUR PABELAN ISLAMIC BOARDING SCHOOL, SEMARANG REGENCY, CENTRAL JAVA - Mukh Nursikin (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this research is how the comprehensive strategy of Islamic boarding schools is to internalize the values of Islamic religious education from the perspective of the Koran to build civil society (Civil Society) at the An-Nur Pabelan Modern Islamic Boarding School, Semarang Regency, Central Java and its implications. This study uses a qualitative-naturalistic approach, collecting data from literature research and field research. Field data through (1) observation, (2) in-depth interviews, and (3) documentation, then followed by the stages of description, reduction, selection, discussion, analysis and conclusion. Research result; the strategy of internalizing Islamic religious education from the perspective of the Koran through the KKNS (student real work class) program with the objectives (1) Developing life skills that have been taught in Islamic boarding schools. (2) Provide new experiences to students about the challenges of living in the future society. (3) Establishing friendly relations between Islamic boarding schools and the community, strategies for studying thematic interpretations and Islamic entrepreneurial training which is attended by the entire santri community and the community around the pesantren. The implication is having a high sense of social solidarity, people really appreciate time, reliable and Islamic human resources (HR), freedom of opinion in self-development, and self-reliance, tolerance in religion, awareness of Islamic life is very strong embedded in each person each society.